The Progressive Spread of the Vascular Wilt Like Pathogen of Calophyllum Detected in Ranomafana National Park, Madagascar - Wright, Patricia Chapple; Otero Jimenez, Beatriz; Rakotonirina, Paul; Andriananoely, Dina H.; Shea, Alexandra; Ratalata, Baovola; Razafimahaimodison, Jean Claude (Frontiers in Forests and Global Change, 2020)
Pathogens are threatening crops worldwide, but little attention has been given to the threat to tree species in undisturbed rainforest. This communication reports the first case of a tree die off caused by a “wilt” in Madagascar. In 2016 while monitoring monthly tree phenology of Ranomafana National Park (RNP), the Centre ValBio research station observed that many Calophyllum adult trees had brown wilted leaves. There are three species of Calophyllum in this rainforest, C. paniculatum, C. drouhardii, and C. milvum, and all three have contracted this pathogen. Our goal was to document the spead of this suspected wilt in Calophyllum trees and determine if site, elevation and DBH had an influence on tree mortality. In 2019 we conducted an inventory of all Calophyllum trees in RNP and 42% of the observed trees were dead. The species with the highest mortality was C. paniculatum, with 53% of trees dead, followed by C. milvum with 18%, and C. drouhardii with only 2% of surveyed trees dead. Bark beetle traces were observed in all dead Calophyllum trees. Tree death caused by this suspected fungal pathogen has spread across a major river in the area and has been found at mid and high elevations. Our results show that C. paniculatum trees with a larger DBH have a higher mortality risk. Our report highlights the importance of fighting invasive pathogens that threaten protected ecosystems.